Approach To Teaching Russian as A Foreign Language With The Use Of Fiction Text (Russian as A Foreign Language) - Niyazova Kh.Kh. (Indonesian Journal Publisher, 2024)
The article is devoted to the methodological peculiarities of using fiction texts in the process of teaching Russian as a foreign language (RFL).The paper deals with the stages of work with a fiction text: pre-textual, textual and post-textual phases. Special attention is paid to the methods that promote the formation of language reflection, understanding of new words through the context, as well as the development of figurative perception of the text.